Grandma's boy - Swardson, Nick 1976-; Wernick, Barry; Covert, Allen 1964-; Wachtel, Waddy (Constantin Film, 2021)
LIfe is sweet for 35-year-old video game tester Alex until he's forced to move in with his overbearing grandmother Lilly and her 2 roommates: oversexed Grace and overmedicated Bea. To save face with his much younger co-workers and sexy new boss, Alex brags about the "three hot babes" living with him, but soon that cat's out of the bag -- and the real party at Grandma's house has just begun!
Special features: Featurettes; Interviews; gelöschte Szenen; Audiokommentare
Keywords: Filmkomödie; Grandmothers / Drama; Video gamers / Drama; Roommates / Drama; Comedy films; Grandmothers; Roommates; Video gamers; Fiction films; Feature films; Drama; Films comiques; Films de fiction; Film; Blu-Ray-Disc